Development of the Migraine‐Related Stigma (MiRS) Questionnaire: Results of the OVERCOME (US) Study - Seng, Elizabeth K.; Muenzel, E. Jolanda; Shapiro, Robert E.; Buse, Dawn C.; Reed, Michael L.; Zagar, Anthony J.; Ashina, Sait; Hutchinson, Susan; Nicholson, Robert A.; Lipton, Richard B. (Headache, 2025)
Background Stigma is emerging as an important social contributor to migraine‐related disability and other outcomes. Currently, there are no published validated measures of migraine‐specific measures of stigma. Objectives This secondary post hoc analysis of a cross‐sectional cohort study aimed to develop a questionnaire to evaluate migraine‐related stigma. Methods Based on focus group discussions among persons with migraine and literature review, a panel of migraine experts iteratively developed 12 candidate items for the migraine‐related stigma (MiRS) questionnaire, which aims to measure if and how people living with migraine perceive they are viewed in a stigmatizing manner by others. The United States ObserVational survey of the Epidemiology tReatment and Care Of MigrainE (OVERCOME) study identified people with active migraine within a demographically representative United States (US) adult sample and administered the novel MiRS questionnaire in addition to questionnaires assessing sociodemographics, monthly headache days, and migraine disability score (Migraine Disability Assessment) among other data. Exploratory factor analysis was then utilized to evaluate the structure of the MiRS items and determine the Cronbach's alpha described internal consistency of the factors. Results This exploratory factor analysis was a secondary post hoc analysis of a cross‐sectional cohort study derived from the OVERCOME population‐based web survey, which was conducted in a United States sample of 61,932 adults with migraine. The mean (standard deviation) age was 41.7 (14.8) years, 74.5% (n = 46,122) were female, and 70.3% (n = 43,564) identified as White. Two factors were identified: MiRS—external perception of Secondary Gain (eigenvalue = 21.5, percentage of total variance = 88.9%) and MiRS—external perception of Minimizing Burden of migraine (eigenvalue = 2.7, percentage of total variance = 11.1%). The two factors were correlated (r = 0.66) and a non‐orthogonal varimax rotation showed that eight items loaded onto the MiRS—Secondary Gain factor, and four items loaded onto the MiRS—Minimizing Burden factor. Conclusion This population‐based study of >60,000 people with migraine allowed the development and validation of the first migraine‐specific measure of perceived external stigma for people with migraine. This study demonstrated that MiRS consists of two internally consistent subscales: Secondary Gain and Minimizing Burden. This may be a useful tool for quantifying perceived migraine‐related stigma to understand determinants of migraine‐related stigma and test interventions to reduce perceived migraine‐related stigma. Plain Language Summary Migraine is a highly burdensome headache disorder, and many people with migraine perceive that others have negative attitudes towards themselves and their disease, which we refer to as stigma. The goal of this study was to develop a set of questions to understand and accurately measure migraine‐related stigma using data from a population‐based survey that included >60,000 adults with migraine. We found that migraine consists of two main factors, which include perceptions that others: (1) believe that people with migraine “use” their disease to achieve secondary gains (unfair advantages like time off of work), and (2) minimize the amount of pain, distress, and disability that the people with migraine experience.